2018
DOI: 10.14434/josotl.v18i2.22539
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Group Size in Interteaching

Abstract: A key component of interteaching, as described by Boyce and Hineline (2002), is the opportunity for students to participate in "dyadic" or pair discussions. Although the rationale for pair discussions is evident, only one study to date has evaluated the relative effectiveness of student performance when group size is manipulated. The present investigation was designed to further evaluate the effect of group size during pair discussions on student quiz scores in an introductory psychology course with a diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…However, Saville et al (2006) and Goto and Schneider (2009) found that students preferred IT. Notably, findings from the present study are similar to those of Rosales and Soldner (2018) in that the perceived results of the two methods did not match the actual results. Students in the present study reported that working in large groups during the LP condition led to hearing more answers and better ideas.…”
Section: Discussioncontrasting
confidence: 67%
“…However, Saville et al (2006) and Goto and Schneider (2009) found that students preferred IT. Notably, findings from the present study are similar to those of Rosales and Soldner (2018) in that the perceived results of the two methods did not match the actual results. Students in the present study reported that working in large groups during the LP condition led to hearing more answers and better ideas.…”
Section: Discussioncontrasting
confidence: 67%
“…3 ). Our analysis provides moderate support for having students work in pairs during discussions, rather than in larger groups (e.g., Boyce & Hineline, 2002 ; Rosales & Soldner, 2018 ). Furthermore, the data suggest that removing the discussion component of interteaching is likely to limit the effectiveness of the approach substantially (e.g., Garcia et al, 2016 ).…”
Section: Discussionmentioning
confidence: 74%
“…Ten studies tested six different variations of interteaching (level of difficulty of prep guides, number of students in the discussion groups, number of quizzes, presence or absence of discussions, presence or absence of lectures, and presence or absence of quality points; Bethke, 2016 ; Garcia et al, 2016 ; Lambert & Saville, 2012 ; Rosales & Soldner, 2018 ; Saville et al, 2011a ; Saville & Zinn, 2009 ) using two different outcome measures (i.e., results of examinations and quizzes). Figure 2 displays a forest plot and the effect-size analyses for these studies (Hedge’s g , standard error, CI, and p -values).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the start of the synchronous peer-guided instruction, the students should have already completed the aforementioned, asynchronous ASR-enhanced brief lecture and read any assigned readings. Upon arriving at the synchronous peer-guided instruction session, the instructor would place the students into small groups (usually 2 to 4 students) using the breakout groups feature of Kaltura Virtual Classroom (see Rosales and Soldner 2018). In the breakout groups, students would be directed to discuss the preparation guide and complete a Record of Interteach form to provide feedback to the instructor about material that was still unclear and also indicate the quality of participation by each member of the small group.…”
Section: Peer-guided Instructionmentioning
confidence: 99%